2023
DOI: 10.1039/d3nr01741a
|View full text |Cite
|
Sign up to set email alerts
|

Prussian blue nanozymes: progress, challenges, and opportunities

Abstract: Prussian Blue Nanozymes (PBNZ) have emerged as a highly efficient agent for reactive oxygen species (ROS) elimination, owing to their multiple enzyme-like properties encompassing catalase (CAT), peroxidase (POD), and superoxide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 120 publications
(164 reference statements)
0
5
0
Order By: Relevance
“…In this nano platform, the drug can be released slowly, which signi cantly improves the therapeutic effect of the drug. In addition, Pb-based nanoplatforms can be designed to have convenient sizes active sites, which can effectively target speci c cells and also help improve drug e cacy [12,13]. However, previous studies have found this regulation less effective under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this nano platform, the drug can be released slowly, which signi cantly improves the therapeutic effect of the drug. In addition, Pb-based nanoplatforms can be designed to have convenient sizes active sites, which can effectively target speci c cells and also help improve drug e cacy [12,13]. However, previous studies have found this regulation less effective under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles of PB and its analogues are recognized as effective PTT agents and have been widely used to combat complex diseases such as cancer and neurodegenerative disorders. 21 The doping performances of PB nanocrystals by Mn, Gd, Cu, Cr, and Zn elements have been studied, 22−26 yet there has been no direct investigation into the doping of PB by Ag + ions, although PB nanocubes decorated with silver nanoparticles were reported. 16 The AgPB nanoparticles exhibit appreciable photothermal effect, and moreover, the releases of Ag + and Fe 2+/3+ ions occur spontaneously under an 808 nm near-infrared (NIR) laser treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To address this limitation, we present the preparation of Ag + ion-doped Prussian blue (AgPB) nanoparticles through a straightforward one-pot reaction, with Ag + ions interstitially displacing a part of K + ions in the PB crystals. Nanoparticles of PB and its analogues are recognized as effective PTT agents and have been widely used to combat complex diseases such as cancer and neurodegenerative disorders . The doping performances of PB nanocrystals by Mn, Gd, Cu, Cr, and Zn elements have been studied, yet there has been no direct investigation into the doping of PB by Ag + ions, although PB nanocubes decorated with silver nanoparticles were reported .…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanozymes in immunosensors and immunoassays is summarized in some reviews [40][41][42], as is their use specifically for food control [43,44]. Several studies have shown that in nanozyme-based LFIAs with catalytic enhancement, the analyte's limit of detection (LOD) can be reduced due to increased coloration in the bands of test strips [30,[45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Before the discovery of catalytic properties, blue-colored Prussian blue was used as a pigment. Later, Prussian blue found application as a peroxidase-mimic catalytic material for the selective reduction of hydrogen peroxide [47,48]. Due to their very high catalytic activity, enzymatic selectivity, ease of synthesis, stability, and low cost, PBNPs are a promising alternative to expensive and insufficiently stable natural peroxidase.…”
Section: Introductionmentioning
confidence: 99%